PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN GAJI TERHADAP KINERJA GURU PEGAWAI NEGERI SIPIL SMA NEGERI COLOMADU, KARANGANYAR - Dwi Mustika Putri; Sutarno Sutarno; Dorothea Ririn Indriastuti (Universitas Slamet Riyadi, 2020)
This research was conducted on SMA Negeri Colomadu Karanganyar which is using qualittiive data and quantitative data. The data resources are secondary data and primary data. The overall population in this study were civil servant teachers at SMA Negeri Colomadu Karanganyar totaling 47 people, the sampel used in this study was taken by 47 respondents. Technical sampling in this research that is used simple census. This research informs that work motivation, work discipline, salary significantly affect performance of PNS teachers.